IMPLEMENTING ALTERNATIVE ASSESSMENTS WITH DESIGN THINKING IN ENGINEERING EDUCATION: ENHANCING OUTCOMES FOR BROADLY-DEFINED ENGINEERING PROBLEMS - Nurhidayah Azmy; Che Maznah Mat Isa (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study examines the use of alternative assessments, integrated with design thinking, in the Integrated Technology Design Project (ITDP) course to improve engineering education outcomes. Traditional assessments often focus on memorization and theoretical knowledge, abandoning practical skills and real-world problem-solving abilities. Additionally, there is a pressing need for alternative assessment approaches that integrate real-world problem-solving skills, fostering a more holistic and applicable skill set among engineering graduates. To address this issue, the study employs a performance criteria matrix (PCM) aligned with course and program outcomes, focusing on seven (7) broadly-defined engineering problems (SP) and relevant knowledge profiles (SK). All 88 students in the ITDP course are evaluated through four types of PCM for Final Project, Presentation, Assignment and Interim Report. The results indicate high student attainment in key program outcomes, especially in problem analysis, modern tool usage, teamwork, and project management. The alternative assessments fulfilled the ETAC Standard 2020 which is aligned to the Graduate Attributes and Professional Competencies (GAPC2021) under the purview of the International Engineering Accords (IEA), effectively promoting practical skills and critical thinking. The study highlights the importance of refining assessment strategies to better align with industry needs and enhance student preparedness for the engineering profession. Future research should explore the new ETAC Standard 2024 requirements via gap analysis, integrating advanced digital tools and simulations, conducting longitudinal studies on the effectiveness of alternative assessments, and increasing industry stakeholder involvement in assessment design. These efforts aim to ensure that assessment strategies remain relevant and effective in preparing graduates for the evolving demands of the engineering field.